1989
DOI: 10.1139/m89-015
|View full text |Cite
|
Sign up to set email alerts
|

Genome structure of Halobacterium halobium: plasmid dynamics in gas vacuole deficient mutants

Abstract: Halobacterium halobium contains two gas vacuole protein genes that are located in plasmid pHH1 (p-vac) and in the chromosomal DNA (c-vac). The mutation frequency for these genes is different: the constitutively expressed p-vac gene is mutated with a frequency of 10(-2), while the chromosomal gene expressed in the stationary phase of growth is mutated with a frequency of 10(-5). The difference in the mutation susceptibility is due to the dynamics of plasmid pHH1. p-vac gene mutations are caused (i) by the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The hypermutable gyp operon and most copies of the ISH are in the plasmid fraction, which is also consistent with the model. In H. salinarium, all characterized mutations are mediated by ISH elements (1,3,(8)(9)(10).…”
mentioning
confidence: 99%
“…The hypermutable gyp operon and most copies of the ISH are in the plasmid fraction, which is also consistent with the model. In H. salinarium, all characterized mutations are mediated by ISH elements (1,3,(8)(9)(10).…”
mentioning
confidence: 99%
“…leading to mutation in phenotypic markers at frequencies of up to 10<-per cell per generation (6,7). Moreover, recombination between repeated copies of the elements occurs so frequently in some strains that a consistent and reproducible map of the genomiie might not exist (1,5,8). Important forces must therefore be acting to limit daimiaee to the genome and to maintain some measure of genetic integritY.…”
Section: Introductionmentioning
confidence: 99%
“…(However, an analysis of gas vesicle gene disruption bN insertion elements [8] showed that the plasmild-enlcoded p-vwc [in FlI DNA] was inactivated more than a thous(and timnes More frequently than the chromosomally-encoded c-l'' in F! DNA].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting transpositional cost to the cell is compounded by the potential recombinational chaos mediated by interaction between members of each insertion sequence family. It has been suggested that a genomically pure clone of H. salinarium cannot be grown because of continual rearrangements which occur in plasmid DNA (27,30,36).The genus Haloferax is not as severely infested with insertion sequences as is H. salinarium. Nevertheless, Haloferax volcanii possesses at least 49 copies of the ISH51 family distributed throughout the genome (8), and there is good evidence for the existence of several other types of repeated sequences as well (35,37).…”
mentioning
confidence: 99%
“…The resulting transpositional cost to the cell is compounded by the potential recombinational chaos mediated by interaction between members of each insertion sequence family. It has been suggested that a genomically pure clone of H. salinarium cannot be grown because of continual rearrangements which occur in plasmid DNA (27,30,36).…”
mentioning
confidence: 99%